2012
DOI: 10.2135/cropsci2011.07.0377
|View full text |Cite
|
Sign up to set email alerts
|

Steer and Plant Responses to Chemical Suppression of Seedhead Emergence in Toxic Endophyte‐Infected Tall Fescue

Abstract: Chaparral herbicide has been shown to suppress seedhead emergence in tall fescue [Lolium arundinaceum (Schreb.) Darbysh] and potentially mitigate the effects of fescue toxicosis. A two‐year grazing experiment evaluated steers grazed on endophyte‐infected fescue–Kentucky bluegrass (Poa pratensis L.) pastures either treated or untreated with Chaparral herbicide to determine if seedhead suppression alleviates fescue toxicosis and increases average daily gain (ADG). Treatments were assigned to six, 3.0‐ha fescue‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
(35 reference statements)
1
36
0
Order By: Relevance
“…The steers used in Experiments 1 and 2 were exposed to differing levels of ergovaline in the pasture for differing lengths of time. While this was a consequence of environmental and experimental design factors in two independent grazing studies [12,13] conducted prior to the present study, the steers biopsied in both experiments had sufficient levels of exposure to cause ergot alkaloid toxicity leading into these experiments. Prior work has demonstrated the onset of a vasoconstrictive effect to dietary ergot alkaloid exposure is fairly rapid.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The steers used in Experiments 1 and 2 were exposed to differing levels of ergovaline in the pasture for differing lengths of time. While this was a consequence of environmental and experimental design factors in two independent grazing studies [12,13] conducted prior to the present study, the steers biopsied in both experiments had sufficient levels of exposure to cause ergot alkaloid toxicity leading into these experiments. Prior work has demonstrated the onset of a vasoconstrictive effect to dietary ergot alkaloid exposure is fairly rapid.…”
Section: Discussionmentioning
confidence: 97%
“…Twenty-four predominantly Angus steers (357 ± 3 kg body weight) grazed E+ Kentucky 31 tall fescue pastures (3 ha) for 126 days during a separate grazing study [12]. The total ergovaline (ergovaline + ergovalinine) concentration of the tall fescue pastures just prior to removal of the steers was 1.35 mg/kg DM.…”
Section: Methodsmentioning
confidence: 99%
“…Distinct visual symptoms of chlorosis following treatment with Chaparral occurred in this study, and the plants remained in this state for a period of approximately 2 weeks. Other reports of chlorosis have been made in other work with this herbicide (Aiken et al, 2012). If this inhibition of photosynthesis occurs when reserves are low, such as in the early spring, tall fescue plants may not have been able to maintain their metabolism during this period of stress, resulting in death of the plants.…”
Section: Application Rate and Date Effects On Seedhead And Plant Densmentioning
confidence: 68%
“…The lack of an impact from an early‐spring application on tall fescue seedhead suppression was somewhat surprising. In previous research, Chaparral (Aiken et al, 2012; Goff et al, 2012a) and other herbicides used to regulate reproductive growth in cool‐season grasses (Glenn et al, 1981; Roberts and Moore, 1990; Moyer and Kelley, 1995) were applied on similar dates (mid to late March) and stages of development (i.e., vegetative) with effective results. The reduced efficacy of the herbicide during this period in this study may be the result of warmer conditions during the winter and early‐spring months of the growing season.…”
Section: Application Rate and Date Effects On Seedhead And Plant Densmentioning
confidence: 99%
“…The active ingredient, Metsulfuron-methyl, does not suppress seed head emergence of Kentucky bluegrass (Poa Pratensis L.) or orchardgrass (Dactylis glomerata L.) Goff, 2012). Aiken et al (2012) reported that in lightly-grazed mixed cool-season grass pastures that were treated or not treated with metsulfuron for seedhead suppression, the incidence of seedheads were nearly 10-fold greater in untreated than treated pastures. Although seedhead emergence declined, forage mass also declined.…”
Section: Chapter I: Introductionmentioning
confidence: 99%